Uma análise de recalques pelo Método de Asaoka modificado com enfoque probabilístico - Schmidt, Celina Aída Bittencourt (1992)
Presents a back analysis of settlements measured from plates under Sarapuís Trial Embankment II, by Modified Asaoka´s Method, to obtain consolidation coefficients and total settlements of local soft clay layer. This embankment is placed at Sarapuí River´s bank, upon a soft clay layer (Sarapuí's soft clay) and is constituted by seven instrumented sections, five of them with vertical drains and two with no vertical drains. Because of the availability of results from several plates, a probabilistic approach is applied to the analysis, makins it possible to obtain confidence intervals instead of an only deterministic result. It"s also performed a comparative evaluation of the different types of drains and an analysis of Modified Asaoka´s Method itself, considering its utilization, limitations and applicability to the problem. The analysis is affected by the way the loads are appliesd and by the development of secondary and primary compression at the same time, which is not expected on the basic hypothesis assumed by the method.